Pelaksanaan Penyidikan Tindak Pidana Pemerasan Dan Pengancaman Yang Dilakukan Melalui Aplikasi Pesan Pada Nomor Seluler Oleh Ditreskrimsus Polda Sumatera Barat - Yenti, Nurlinda; Pamungkas, Yoga (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
The development of technology is directly proportional to the phenomenon of crime by utilizing electronic media. The government issued a special legal product to accommodate the development of criminal acts committed through electronic means, namely Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. One of the most common crimes committed by means of communication is extortion and threats, as stated in the Police Report Number: LP/111/III/2021/SPKT-SBR. The formulation of the problem in this study is how to carry out investigations into criminal acts of extortion and threats carried out through a message application on a cellular number by the DitreskrimsusPolda West Sumatra on police reports number LP/111/III/2021/SPKT-SBR?. What are the obstacles in carrying out investigations into criminal acts of extortion and threats carried out through a message application on a cellular number by the DitreskrimsusPolda West Sumatra on the police report number LP/111/III/2021/SPKT-SBR?.What are the obstacles in carrying out investigations into criminal acts of extortion and threats carried out through a message application on a cellular number by the DitreskrimsusPolda West Sumatra on the police report number LP/111/III/2021/SPKT-SBR?. The approach used in this research is sociological juridical, namely the problem approach by looking at the reality in the field associated with the applicable rules. The results of the research and discussion are starting from reports of victims who have been threatened with the distribution of personal photos of victims who violate decency aimed at eradicating the suspect's debt to the victim by corroborating evidence of electronic documents containing screenshots of conversations and vulgar photos of victims sent to the victim's parents. so that the suspect is proven to have violated Article 27 paragraph (1) Juncto Article 27 paragraph (4) Juncto Article 29 Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. Constraints include internal constraints, namely the lack of competent human resources and computer forensics equipment, there is no special regulation that authorizes cyber investigators to access data on individuals suspected of committing crimes.